Implementasi dan Evaluasi Penerapan Globus Toolkit untuk Aplikasi Grid Computing - Budiharto, Widodo (Bina Nusantara University, 2012)
Grid computing is a distributed computing technology that utilizes resources connected through a free computer network, yet coordinated with a specific mechanism. The development of grid computing infrastructure is not easy because it takes skill and experience in the installation and configuration of both Linux-based and open source program. In this study, the author built a grid computing infrastructure based on Debian 4, and used Globus Toolkit 4.1.2 on three computers. The WSRF technology was tried to run as an indication that the grid infrastructure has been successfully built. Based on some experiments in this study, grid computing can run well on the three computers with a user interface of web-based grid system using the UCLA Grid Portal. Overall the system runs fine, but it requires high experiences and comprehensions upon the Linux operating systems as well as computer networks in the installation process.